2020
DOI: 10.1186/s12906-020-03020-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of volatile active components in Acori Tatarinowii Rhizome essential oil from different regions in China by C6 glioma cells

Abstract: Background: Acori Tatarinowii Rhizome (ATR) is a well-recognized Chinese herbal medicine prescribed to treat neurological disorders. The essential oil (ATEO) is considered as the active fraction of ATR and the content of ATEO is used as the only indicator for ATR content determination. The quality of ATEO varies widely due to region difference; however, little is known about how to study ATEO quality chemically and biologically in response to region difference. Thus, it is of great importance to identify volat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The chemical constituents of the EOs of ATR mainly contain lignans, phenylpropanoids, and terpenoids. , Among them, asarone-based phenylpropanoids (α-asarone and β-asarone) are the characteristic constituents. As a type of solvent extraction device, a Soxhlet extractor (Figure S1) has its own advantages in EO extraction .…”
Section: Resultsmentioning
confidence: 99%
“…The chemical constituents of the EOs of ATR mainly contain lignans, phenylpropanoids, and terpenoids. , Among them, asarone-based phenylpropanoids (α-asarone and β-asarone) are the characteristic constituents. As a type of solvent extraction device, a Soxhlet extractor (Figure S1) has its own advantages in EO extraction .…”
Section: Resultsmentioning
confidence: 99%
“…Acori Tatarinowii Rhizoma (Shichangpu in Chinese) is the dried rhizome of Acorus tatarinowii Schott and has been used in traditional Chinese medicine for the treatment of neurological disorders. 17 α‐Asarone is a simple phenylpropanoids in Acori Tatarinowii Rhizoma, exerting beneficial effects on alleviating neuronal excitotoxicity, anti‐inflammation and neurotransmission, and these studies are mainly focused on the regulation of central nervous system. 18 , 19 , 20 However, the role of α‐asarone in peripheral regulation against depression remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…82 Various studies have reported its sedative, antidepressant, digestive, analgesic, diuretic, and antifungal effects. [83][84][85][86] Two new spiro alkaloids that have a naturally unusual morpholine ring in their structure, called Acortatarins A (D2) and B (D3), were isolated in 2011 from the rhizome of Acorus tatarinowii. The AO capacities of compounds D2 and D3 were determined, according to the percentage of ROS production inhibition induced by glucose in mesangial cells.…”
Section: Introductionmentioning
confidence: 99%